Inflation expectations and risk premia in emerging bond markets: Evidence from Mexico - Remy Beauregard; Jens H. E. Christensen; Eric Fischer; Simon Zhu (Federal Reserve Bank of New York, 2021)
To study inflation expectations and associated risk premia in emerging bond markets, this paper provides estimates for Mexico based on an arbitrage-free dynamic term structure model of nominal and real bond prices that accounts for their liquidity risk. In addition to documenting the existence of large and time-varying liquidity premia in nominal and real bond prices that are only weakly correlated, the results indicate that long-term inflation expectations in Mexico are well anchored close to the inflation target of the Bank of Mexico. Furthermore, Mexican inflation risk premia are larger and more volatile than those in Canada and the United States.
Keywords: D84; E31; E47; E52; E58; G12; 330; term structure modeling; liquidity risk; financial market frictions; central bank credibility